AB0018 Tubulointerstitial injury in lupus nephritis and gene expresion of KIM-1. (23rd January 2014) - Mas, L.; Hayes Salinas, M.; Retamozo, S.; Saurit, V.; Caeiro, F.; Diller, A.; De la Fuente, J.; Trujillo Salazar, P.; Alvarellos, A.; Alvarellos, T.
Abstract : Background: The extent of tubular lesions and recruitment of inflammatory cells is belived to be and important predictor of renal function in immune- mediated glomerulonephritis (1) such as Lupus Nephritis (LN). The response of the renal tubules to proteinuria is implicated in progression of renal disease (2). Kidney Injury Molecule 1 (KIM-1), a recently discovered transmembrane tubular protein, is markedly induced in acute kidney injury and chronic kidney disease. KIM-1 is an ideal biomarker because is not expressed in normal kidney but specifically expressed in injured proximal tubular cells and such expression persist until the damage cells recovered (3). Objectives: The role of KIM-1 in LN remains elusive. In this study, we examined the correlation between gene expression of KIM-1 in the urinary sediment and biopsy of patients (P) with NL diagnosis, and the relationship between KIM-1 expression and urine Protein/Creatinine ratio (P/C). Methods: Twenty two kidney biopsies and 28 urine samples from 20 P with LN (17 F/3 M, age 33, 55±12, 28; Range: 15-72) were evaluated. Kidney biopsies were classified according to ISN/RPS scoring system (4). Urine samples from LN patients were divided as P/C <1 (Group I, N=12) and P/C >1 (Group II, N=16), and urine samples from healthy individuals (Group III, N=17) were analized as control. Levels of gene expression of KIM-1 were evaluated using Quantitative Real Time PCR (QPCR). All amplifications were carried out in duplicate and threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting the corresponding β2Microglobuline (β2M) control, or DCt=Ct, gene - Ct, B2M . A Spearman's rank-order correlations (r) was used to test associations between gene expression levels in biopsy and urine pairs samples. To test for differential gene expression between groups a variance analysis (ANOVA) was performed. Results: We observed a significant correlation between biopsy and urine, Spearman r=0, 6838 (p=0.0005). There were a statistically significant difference in the expression of KIM-1 between groups (p=0, 0110). After ANOVA test, we observed that the levels of mRNA of KIM-1 in Group II were higher than those from Group I and there were higher than Group III. Conclusions: There was no expression of KIM-1 in normal urine. In LN, urinary KIM-1 gene expression is closely related to tissue KIM-1 and correlates with the severity of tubular interstitial injury. Quantitation of urinary KIM-1 is likely to be a nobel noninvasive and sensitive method for the evaluation of kidney injury in P with LN. References: Zheng L, et al. Journal of Histochemistry and Cytochemistry. 56(5): 517-529, 2008. Hill G, et al. Kidney International. 60: 1893-1903, 2001. Hou W, et al. Transplantation Reviews. 24:143-146, 2010. Weening JJ, et al. Kidney International. 65 (2): 521-530, 2004. Disclosure of Interest: None Declared